Beispiele für den Einsatz von Automatisierungstechnik bei der Analyse biologischer Modellorganismen - Marcato, Daniel; Breitwieser, Helmut; Scheikl, Paul Maria; Peravali, Ravindra; Reischl, Markus; Pylatiuk, Christian (At-Automatisierungstechnik, 2016)
In order to experiment with biological model organisms, manual sample preparation is usually necessary. With zebrafish eggs this means manual pipetting into microtiter plates, before they can be used in any chemical or behavioral studies. The analysis of the resulting data is most of the time also still done manually. Thus systems for the automation of these steps were developed at the Institute for Applied Computer Science. The chosen examples include the automated sorting of zebrafish eggs via a robot capable of functioning without visible light, the detection of motor reactions in zebrafish embryos in response to optical stimuli as well as a system for automated behavioral studies of adult fish.
Created from Fastlane, Scopus look-up
Keywords: bio-analysis technology; feature analysis; microscopy; model organism; Sorting robot; zebrafish